The Effect of Using Pop Up Book Media on Critical Thinking Ability - Ramadhani, Sri; Putri Yanti Pulungan, Dwi; Sitepu*, Melyani Sari (Riwayat: Educational Journal of History and Humanities, 2024)
The first formal level of education which is part of the education series in Indonesia is elementary school. Therefore, the role of educators or teachers in elementary schools is to bring as much knowledge as possible to this world in the child's activity environment, both internally and externally as a learning experience. One way educators can support children's learning process in another way is by providing creative and innovative learning media to stimulate interest in learning and foster children's critical thinking abilities. Students must have the courage to accept challenges to try new things. Dare to try means accepting and analyzing problems, and finding solutions to these problems. The learning process requires critical thinking skills to achieve effective learning.